O casamento de Leonor e Frederico III (1451-1452) e as relações entre Portugal e o Sacro Império nos finais da Idade Média - António Martins Costa (Medievalista)
In the late Middle Ages, the young dynasty of Avis, after linked by kinship to England, Aragon and Burgundy, attempts to create in the space of Christianity a connection at the highest level: the Holy Roman Empire. With the marriage of the princess Leonor and Frederick III, arranged between 1451 and 1452, king Afonso V played not only with a process of affirmation of his Crown but also with the legitimation of his lineage, granting the Rex Romanorum the right bride to establish the Habsburg House on the imperial throne. The development of the historiography of medieval international relations in the last decades has given the pretext to observe the political approximation of those two kingdoms, geographically distant, based on an important royal marriage that has given us a considerable set of primary sources (chronicles, documents and iconography). Initially, we will try to analyze the dynamics of the alliances that have resulted in that matrimonial interest; in a second phase, considering the progress of diplomacy, we will follow the negotiation process between the Crowns; finally, we will observe the different phases of royal marriage (from Portugal to Italy), which foresee a new cycle of relations between the Avis and Habsburg dynasties.